Give us a rope! (Journal of Parents and Teachers, 2014)
The Department of guidance began as a neglected department in the schools, and every day is taking more and more importance, mainly between the families. Parents, disoriented and insecure, need the support and help that is provided from this Department. This article explains its importance and when to ask for help.
Keywords: Department of guidance; counselor; help; families.